Antibacterial bamboo wood based on L-DOPA and PEI grafted nano-silver coating and preparation method of antibacterial bamboo wood

By forming L-DOPA and PEI grafted nanosilver coatings on the surface of bamboo, the problem of insufficient environmental protection and interface compatibility of antibacterial agents in bamboo antibacterial technology is solved, and the antibacterial properties and anti-mold effect of bamboo are significantly improved.

CN119188937APending Publication Date: 2024-12-27ZHEJIANG SHENGHUA YUNFENG GREENEO +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411459761.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing antibacterial technology of bamboo has shortcomings in improving the environmental protection and interface compatibility of antibacterial agents, and it is difficult to effectively improve the antibacterial performance of bamboo.

Method used

Using levodopa (L-DOPA) and trimethylolamide (PEI) grafted nanosilver coating, the spontaneous polymerization of L-DOPA and accelerated aggregate formation of PEI can achieve silver mirror reaction to generate nanosilver, improving the Antibacterial properties of bamboo.

Benefits of technology

The antibacterial properties of bamboo are significantly improved. After treatment, the antibacterial rate of bamboo to E. coli and Staphylococcus aureus reaches 100%, and the growth of mold is significantly reduced and the anti-mold performance of bamboo is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119188937A_ABST
    Figure CN119188937A_ABST
Patent Text Reader

Abstract

The invention provides an antibacterial bamboo based on an L-DOPA and PEI grafted nano-silver coating, the antibacterial bamboo comprises a bamboo, a polymer film attached to the surface of the bamboo and nano-silver grafted on the surface of the polymer film, and the polymer film is an L-DOPA polymer and / or an L-DOPA / PEI polymer. The antibacterial agent based on the L-D / PEI / Ag coating is formed by grafting nano-silver on the surface of the bamboo wood by using green and environment-friendly biological adhesive L-DOPA and trihydroxymethyl aminomethane PEI. The L-DOPA and catechol derivatives thereof can be spontaneously polymerized to form a firm polymer composite layer which is strongly attached to the surface of the bamboo wood, so that the interfacial compatibility of the bamboo wood and the coating is improved, the addition of the PEI can effectively accelerate the formation of aggregate, the construction of the L-DOPA / PEI coating is realized, and the service life of the coating is prolonged. Silver ions can be subjected to a silver mirror reaction with a catechol structure existing on the surface of the modified bamboo wood to generate nano-silver, and the nano-silver has good antibacterial property, so that the antibacterial property of the bamboo wood is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to antibacterial bamboo material, and in particular to a method for preparing antibacterial bamboo material based on L-DOPA and PEI grafted nano silver coating. Background Art

[0002] my country has abundant bamboo resources, but the development and utilization is far from enough. This is also related to the properties of bamboo itself. Bamboo has the advantages of short growth cycle, high strength, good toughness, degradability and sustainability. However, the structure of bamboo is mainly fiber cells, thin-walled cells and vessels, mainly composed of cellulose, hemicellulose and lignin. Compared with wood, bamboo also contains relatively more starch, sugar, protein and other substances, which makes bamboo susceptible to bacteria and insects, resulting in mildew, decay and other phenomena. Therefore, in order to expand the high-value-added utilization of bamboo resources, it is particularly important to improve its antibacterial properties.

[0003] At present, the use of chemical agents to impregnate or coat the surface of bamboo is more common in the antibacterial treatment of bamboo. Regarding antibacterial agents, there are studies that use atom transfer radical polymerization (ATRP) to graft the quaternary ammonium group in dimethyldiallylammonium chloride onto the surface of nano-xylan macromolecular initiator to obtain modified nano-xylan biological antibacterial agents. Nanosilver has good antibacterial properties and can be prepared by in-situ growth of silver nanoparticles (AgNPs) and 1H, 1H, 2H, 2H-perfluorodecathiol (PFDT) deposition to prepare multifunctional bamboo materials with superhydrophobicity, self-cleaning properties, dimensional stability, conductivity, flame retardancy and antibacterial activity. Regarding the current antibacterial processes for bamboo, there are also technologies that use spray drying technology, water-in-oil emulsions, nanoemulsions, and molecular complex embedding technology to prepare citral microcapsules, and technologies that combine synthetic antioxidants and natural antioxidants, which are used in bamboo antibacterial. Using the characteristics of biological enzyme catalytic oxidation, using non-toxic fungicide iodine to form a stable chemical bond with bamboo to improve the anti-loss of iodine and enhance the mildew resistance of bamboo.

[0004] The current research on the antibacterial properties of bamboo is very valuable and meaningful, but further work is still needed to improve the interfacial compatibility between bamboo and antimicrobial agents and to enhance the environmental friendliness and antibacterial effects of antimicrobial agents. Summary of the invention

[0005] The present invention proposes to form an antibacterial agent based on LD / PEI / Ag coating by grafting nanosilver on the surface of bamboo using green and environmentally friendly bioadhesives levodopa L-DOPA and tris(hydroxymethyl)aminomethane PEI). L-DOPA and its catechol derivatives can spontaneously polymerize to form a solid polymer composite layer strongly attached to the surface of bamboo, thereby improving the interfacial compatibility between bamboo and coating. The addition of PEI can effectively accelerate the formation of aggregates and realize the construction of L-DOPA / PEI coating. Silver ions can react with catechol structures existing on the surface of modified bamboo to generate nanosilver. Nanosilver has good antibacterial properties, thereby effectively improving the antibacterial properties of bamboo.

[0006] The invention provides an antibacterial bamboo material based on L-DOPA and PEI grafted nano-silver coating. The antibacterial bamboo material comprises bamboo material, a polymer film attached to the surface of the bamboo material and nano-silver grafted on the surface of the polymer film. The polymer film is L-DOPA polymer and / or L-DOPA / PEI polymer.

[0007] In some embodiments of the present invention, the method for preparing the antibacterial bamboo material comprises:

[0008] Step 1) sawing the bamboo after removing the green bamboo into bamboo blocks of different sizes, cleaning the surface of the bamboo blocks with ultrapure water and anhydrous ethanol, and vacuum drying, and the obtained samples are marked as BT;

[0009] Step 2) Pour L-DOPA into water and stir evenly, adjust the pH of the solution to 7-10, and mark the prepared solution as LD;

[0010] Or pour L-DOPA into water and stir evenly, add PEI, adjust the solution pH to 7-10, and mark the prepared solution as LD / PEI;

[0011] Step 3) putting the bamboo block BT into the LD or LD / PEI solution prepared in step 2), stirring, taking out the bamboo block, washing, drying, and marking the obtained samples as BT / LD or BT / LD / PEI respectively;

[0012] Step 4) prepares a silver ion solution, protects from light, and seals the samples of step 3) in the silver ion solution to react in a dark place to obtain antibacterial bamboo material.

[0013] In some embodiments, the concentration of LD and LD / PEI solutions in step 2) is 1 g / L-10 g / L, and the concentration of the silver ion solution is 1 g / L-5 g / L.

[0014] In some embodiments, the mass ratio of L-DOPA to PEI is 1-5:1-5.

[0015] In some embodiments, the step 1) includes: sawing the bamboo after removing the green bamboo into bamboo blocks with a size of 20×20×6 mm, washing the surface of the bamboo block twice with ultrapure water and anhydrous ethanol respectively to wash away obvious stains on the surface of the bamboo block, and then placing it in a vacuum drying oven, and drying it at 50-70°C for 24-72 hours, and then taking it out for use, and the obtained sample is marked as BT.

[0016] In some embodiments, the step 2) comprises: weighing L-DOPA and pouring it into water, stirring it evenly, and then adjusting the pH of the solution to 8.5 with Tris solution, and the prepared solution is marked as LD.

[0017] In some embodiments, the step 2) includes: weighing L-DOPA and pouring it into water, then adding polyethyleneimine, stirring evenly, adjusting the pH of the solution to 8.5 with HCl-Tris buffer solution, and the prepared solution is marked as LD / PEI.

[0018] In some embodiments, the step 3) includes: adding bamboo block BT to the prepared LD solution or LD / PEI solution, and stirring at a constant temperature of 50-70°C in a magnetic stirring oil bath for 5-8 hours; finally, taking out the stirred bamboo block, washing it twice with deionized water, and placing it in an oven and drying it at a constant temperature of 50-70°C for 4-8 hours.

[0019] In some embodiments, the step 4) includes: pouring AgNO3 into water, wrapping the surface of the beaker with tin foil until it is opaque, then placing the samples BT / LD and BT / LD / PEI into silver nitrate solutions respectively, sealing the mouth of the beaker with tin foil, and placing the beaker in a magnetic stirring oil bath at 30-60°C and stirring at a constant temperature for 3-8 hours, finally taking out the bamboo block, washing it twice with ultrapure water until it is neutral, and placing it in a drying oven and drying it at a constant temperature of 50-70°C for 4-8 hours.

[0020] In some embodiments, step 1) sawing the bamboo after removing the bamboo green into bamboo blocks with a size of 20×20×6 mm, using ultrapure water and anhydrous ethanol to clean the surface of the bamboo blocks twice respectively to wash off obvious stains on the surface of the bamboo blocks, and then putting them into a vacuum drying oven, and drying them at 60°C for 72 hours, and then taking them out for use, and the obtained sample is marked as BT; step 2) weighing L-DOPA, pouring it into water, and then adding polyethyleneimine (PEI), stirring evenly, adjusting the solution pH to 8.5 with HCl-Tris buffer solution, and the prepared solution is marked as LD / PEI; step 3) adding bamboo block BT to the prepared LD / PEI solution, and stirring at a constant temperature of 60°C in a magnetic stirring oil bath for 8 hours. Finally, the stirred bamboo pieces were taken out, washed twice with deionized water, and dried in an oven at 60°C for 6 hours. The obtained samples were marked as BT / LD / PEI respectively. Step 4) AgNO3 was weighed and poured into water. The surface of the beaker was wrapped with tin foil until it was opaque. Then, the samples BT / LD and BT / LD / PEI were respectively placed in a silver nitrate solution, the mouth of the beaker was sealed with tin foil, and the beaker was placed in a magnetic stirring oil bath at 40°C for constant temperature stirring for 6 hours. Finally, the bamboo pieces were taken out, washed twice with ultrapure water until neutral, and dried in a drying oven at 60°C for 6 hours.

[0021] The preparation flow chart and reaction mechanism of the bamboo surface grafted LD / PEI and nano silver coating provided by the present invention are as follows: Figure 1 As shown in the figure, L-DOPA and its catechol derivatives self-polymerize to form a solid polymer layer attached to the surface of bamboo. The addition of PEI can effectively accelerate the formation of aggregates and realize the construction of L-DOPA / PEI coating. The catechol structures in L-DOPA polymer and L-DOPA / PEI polymer are then in situ reduced with silver ions through chelation to form nanosilver coating. The samples obtained are marked as BT / LD / Ag and BT / LD / PEI / Ag, respectively.

[0022] In some embodiments, the bamboo blocks before and after treatment were tested for anti-E. coli* and Staphylococcus aureus*, and the test results showed that the antibacterial rates of BT / LD / Ag and BT / LD / PEI / Ag after bamboo modification were 100%, the antibacterial rates of untreated bamboo blocks BT against E. coli and Staphylococcus aureus were 45.3% and 57.8%, respectively, and the antibacterial rates of BT / LD / Ag and BT / LD / PEI / Ag after treatment were increased by 54.7% and 42.2%, respectively. Therefore, bamboo can effectively resist common bacteria by surface modification of LD and PEI grafted nanosilver.

[0023] In some embodiments, by conducting an anti-Aspergillus niger test on the bamboo before and after treatment, the test results show that after 5 days of cultivation, there is significantly more mold growth on the surfaces of BT and BT / LD, and the number of mold on the surfaces of BT / LD / Ag and BT / LD / PEI / Ag is relatively small; after 7 days of cultivation, the surfaces of BT and BT / LD are almost covered with Aspergillus niger, but the surfaces of BT / LD / Ag and BT / LD / PEI / Ag have a relatively small amount of Aspergillus niger, and the modification effect of BT / LD / Ag is better than that of BT / LD / PEI / Ag in terms of anti-mold. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Preparation and mechanism of bamboo modified by L-DOPA and PEI grafted with nanosilver

[0025] Figure 2 XRD analysis of bamboo modified by L-DOPA and PEI grafted with nanosilver;

[0026] Figure 3 To test the antibacterial properties of bamboo modified by L-DOPA and PEI grafted with nanosilver;

[0027] Figure 4 To test the antifungal properties of bamboo modified with L-DOPA and PEI grafted with nanosilver. DETAILED DESCRIPTION

[0028] The materials used in the following examples are as follows:

[0029] The bamboo material is moso bamboo that has been treated with bamboo leaves and grows in Hengyang, Hunan.

[0030] L-DOPA (levodopa) (purity 99%) and PEI (tris(hydroxymethyl)aminomethane) were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0031] Polyethyleneimine (purity 99%), silver nitrate (purity 99%), hydrochloric acid and other analytical grade reagents were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. All chemical reagents were used without further purification, and deionized water was used in all experiments.

[0032] Example 1 Preparation of BT / LD / Ag

[0033] Step 1) sawing the bamboo after removing the green bamboo into bamboo blocks with a size of 20×20×6 mm, washing the surface of the bamboo block twice with ultrapure water and anhydrous ethanol respectively to wash away obvious stains on the surface of the bamboo block, and then putting it into a vacuum drying oven and drying it at 60° C. for 72 hours before taking it out for use, and the obtained sample is marked as BT;

[0034] Step 2) Weigh 1 g of levodopa (L-DOPA), pour it into a beaker filled with 500 mL of water, stir it evenly, and then adjust the pH of the solution to 8.5 with Tris solution (tris(hydroxymethyl)aminomethane solution). The prepared solution is marked as LD;

[0035] Step 3) Add bamboo block BT to the prepared LD solution and stir it in a magnetic stirring oil bath at 60°C for 8 hours; finally, take out the stirred bamboo block, wash it twice with deionized water, put it in an oven and dry it at 60°C for 6 hours, and the obtained samples are marked as BT / LD;

[0036] Step 4) Weigh 0.5 g of AgNO3 and pour it into a beaker filled with 500 mL of water. Wrap the surface of the beaker with tin foil until it is opaque. Then put the sample BT / LD into the silver nitrate solution, seal the mouth of the beaker with tin foil, and put the beaker into a magnetic stirring oil bath at 40°C and stir at this temperature for 6 hours. Finally, take out the bamboo block, wash it twice with ultrapure water until it is neutral, and put it into a drying oven and dry it at a constant temperature of 60°C for 6 hours.

[0037] Example 2 BT / LD / PEI / Ag

[0038] Step 1) sawing the bamboo after removing the green bamboo into bamboo blocks with a size of 20×20×6 mm, washing the surface of the bamboo block twice with ultrapure water and anhydrous ethanol respectively to wash away obvious stains on the surface of the bamboo block, and then putting it into a vacuum drying oven and drying it at 60° C. for 72 hours before taking it out for use, and the obtained sample is marked as BT;

[0039] Step 2) Weigh 1 g of L-DOPA and pour it into a beaker filled with 500 mL of water, then add 1 g of polyethyleneimine (PEI), stir evenly, and adjust the pH of the solution to 8.5 with HCl-Tris buffer solution. The prepared solution is marked as LD / PEI;

[0040] Step 3) Add bamboo block BT to the prepared LD / PEI solution and stir it in a magnetic stirring oil bath at 60°C for 8 hours. Finally, take out the stirred bamboo block, wash it twice with deionized water, put it in an oven and dry it at 60°C for 6 hours. The obtained samples are marked as BT / LD / PEI;

[0041] Step 4) Weigh 0.5 g of AgNO3 and pour it into a beaker filled with 500 mL of water. Wrap the surface of the beaker with tin foil until it is opaque. Then put the samples BT / LD and BT / LD / PEI into the silver nitrate solution respectively, seal the mouth of the beaker with tin foil, and put the beaker into a magnetic stirring oil bath at 40°C and stir at constant temperature for 6 hours. Finally, take out the bamboo block, wash it twice with ultrapure water until it is neutral, and put it into a drying oven at 60°C for constant temperature drying for 6 hours.

[0042] Example 3 Performance Characterization Method

[0043] The crystal structure and modification effect of the bamboo before and after modification were analyzed by X-ray diffraction (XRD, X'Pert3 Powder, PANalytical BV, Netherlands) of the bamboo BT before modification (the sample obtained in step 1 of Example 1) and the bamboo BT / LD after modification (the sample obtained in step 3 of Example 1), BT / LD / Ag (the sample obtained in Example 1), and BT / LD / PEI / Ag (the sample obtained in Example 2). The radiation source was Cu Kα and the wavelength was The tube voltage is 40kV, the tube current is stable at 40mA, and the test angle is from 10° to 80°.

[0044] The crystal structure of BT before and after modification and the modified grafting effect were analyzed by XRD. Figure 2 As shown in the figure, (101) and (002) are the diffraction peaks of the cellulose crystal plane in bamboo. The BT / LD / Ag and BT / LD / PEI / Ag modification treatments did not change the cellulose crystal structure. The diffraction peaks of the (111), (200), (220) and (311) crystal planes of Ag are at 2θ of 38.1°, 44.2°, 64.4° and 77.3° respectively. The research results show that the diffraction peaks of Ag can be clearly observed after the modification treatment, proving that silver particles are successfully grafted on the BT surface.

[0045] Example 4 Antibacterial Test

[0046] The Escherichia coli and Staphylococcus aureus colonies were inoculated with meat extract peptone (LB) liquid medium, and cultured at 37°C and 130r / min for 18h. The bacterial suspension was diluted with broth to a viable count of about 105cfu / mL before testing. Then, 5mL of the diluted bacterial suspension was added to the conical flask, and the bamboo blocks were prepared into 0.75g square samples and placed in the conical flask after sterilization and sealed with sterile sealing film. The conical flask was placed in a water bath oscillator at 24°C and 150r / min for 18h. After the culture was completed, the solution after the antibacterial test was diluted with 0.03mol / LPBS buffer to a viable count of about 105cfu / mL. Take 100μL of the diluted bacterial solution and evenly apply it on the nutrient agar medium. After the culture dish was cultured at 37°C in a bacterial incubator for 24-48h, the number of colonies on the surface was counted to obtain the antibacterial activity of the sample.

[0047]

[0048] Y——inhibition rate;

[0049] W b——The viable bacterial concentration of the standard blank sample after oscillation for 18 hours;

[0050] W c ——Concentration of viable bacteria in antibacterial bamboo blocks / non-antibacterial bamboo blocks after oscillation for 18 hours.

[0051] Aspergillus niger was cultured on potato dextrose agar (PDA) medium. In a sterile environment, Aspergillus niger was inoculated on the medium and sealed with a sealing film. It was placed in a constant humidity incubator for 3 days. The temperature of the constant temperature incubator was set at 25°C and the relative humidity was maintained at 85%. Then 100uL of bacterial suspension was injected into the culture dish, and the surface of the culture medium was evenly smeared with a triangular glass rod. The sample was carefully placed in the center of the culture dish, and it was sealed with a sterile sealing film and returned to the constant temperature and humidity incubator. Observe once every other day and record the growth status of hyphae and spores on the surface of the sample.

[0052] The bamboo blocks before and after treatment were tested for resistance to E. coli* and Staphylococcus aureus*. Figure 3 The test results show that the antibacterial rates of BT / LD / Ag and BT / LD / PEI / Ag after bamboo modification are 100% (Table 1). The antibacterial rates of untreated bamboo BT against Escherichia coli and Staphylococcus aureus are 45.3% and 57.8%, respectively. The antibacterial rates of BT / LD / Ag and BT / LD / PEI / Ag after treatment are increased by 54.7% and 42.2%, respectively. Therefore, bamboo can effectively resist common bacteria by surface modification of LD and PEI grafted nanosilver.

[0053] Table 1 Antibacterial rate of bamboo modified by L-DOPA and PEI grafted with nanosilver

[0054]

[0055] * The dilution factor is 10 -4

[0056] Example 6 Results of Anti-Mold

[0057] By testing the bamboo before and after treatment for resistance to Aspergillus niger, Figure 4 As shown, the test results show that after 5 days of cultivation, there is significantly more mold growth on the surface of BT and BT / LD, and the number of molds on the surface of BT / LD / Ag and BT / LD / PEI / Ag is relatively small. After 7 days of cultivation, the surface of BT and BT / LD is almost full of Aspergillus niger, but the surface of BT / LD / Ag and BT / LD / PEI / Ag has a relatively small amount of Aspergillus niger, and the modification effect of BT / LD / Ag is better than BT / LD / PEI / Ag in terms of anti-mold.

Claims

1. An antibacterial bamboo material based on L-DOPA and PEI grafted nano-silver coating, characterized in that: The antibacterial bamboo material comprises bamboo material, a polymer film attached to the surface of the bamboo material, and nanosilver grafted on the surface of the polymer film, wherein the polymer film is an L-DOPA polymer and / or an L-DOPA / PEI polymer. The preparation method of the antibacterial bamboo material comprises: Step 1) sawing the bamboo after removing the green bamboo into bamboo blocks of different sizes, cleaning the surface of the bamboo blocks with ultrapure water and anhydrous ethanol, and vacuum drying, and the obtained samples are marked as BT; Step 2) Pour L-DOPA into water and stir evenly, adjust the pH of the solution to 7-10, and mark the prepared solution as LD; Or pour L-DOPA into water and stir evenly, add PEI, adjust the solution pH to 7-10, and mark the prepared solution as LD / PEI; Step 3) putting the bamboo block BT into the LD or LD / PEI solution prepared in step 2), stirring, taking out the bamboo block, washing, drying, and the obtained samples are marked as BT / LD or BT / LD / PEI respectively; Step 4) prepares a silver ion solution, protects from light, and seals the samples of step 3) in the silver ion solution to react in a dark place to obtain antibacterial bamboo material.

2. The antibacterial bamboo material based on L-DOPA and PEI grafted nano-silver coating according to claim 1, characterized in that: The concentration of LD and LD / PEI solutions in step 2) is 1g / L-10g / L, and the concentration of the silver ion solution is 1g / L-5g / L.

3. The antibacterial bamboo material based on L-DOPA and PEI grafted nano-silver coating according to claim 1, characterized in that: The mass ratio of L-DOPA to PEI is 1-5:1-5.

4. The antibacterial bamboo material based on L-DOPA and PEI grafted nano-silver coating according to claim 1, characterized in that: The step 1) comprises: sawing the bamboo after removing the green bamboo into bamboo blocks with a size of 20×20×6 mm, washing the surface of the bamboo block twice with ultrapure water and anhydrous ethanol respectively to wash away obvious stains on the surface of the bamboo block, then placing it in a vacuum drying oven, and drying it at 50-70° C. for 24-72 hours, then taking it out for use, and the obtained sample is marked as BT.

5. The antibacterial bamboo material based on L-DOPA and PEI grafted nano-silver coating according to claim 1, characterized in that: The step 2) comprises: weighing L-DOPA and pouring it into water, stirring it evenly, and then adjusting the pH of the solution to 8.5 with Tris solution, and the prepared solution is marked as LD.

6. The antibacterial bamboo material based on L-DOPA and PEI grafted nano-silver coating according to claim 1, characterized in that: The step 2) comprises: weighing L-DOPA and pouring it into water, then adding polyethyleneimine, stirring evenly, adjusting the pH of the solution to 8.5 with HCl-Tris buffer solution, and the prepared solution is marked as LD / PEI.

7. The antibacterial bamboo material based on L-DOPA and PEI grafted nano-silver coating according to claim 1, characterized in that: The step 3) comprises: adding bamboo blocks BT to the prepared LD solution or LD / PEI solution, and stirring the bamboo blocks in a magnetic stirring oil bath at 50-70° C. for 5-8 hours; finally, taking out the stirred bamboo blocks, washing them twice with deionized water, and placing them in an oven for constant temperature drying at 50-70° C. for 4-8 hours.

8. The antibacterial bamboo material based on L-DOPA and PEI grafted nano-silver coating according to claim 1, characterized in that: The step 4) comprises: pouring AgNO3 into water, wrapping the surface of the beaker with tin foil until it is opaque, then placing the samples BT / LD and BT / LD / PEI into silver nitrate solution respectively, sealing the mouth of the beaker with tin foil, and placing the beaker in a magnetic stirring oil bath at 30-60°C for constant temperature stirring for 3-8 hours, and finally taking out the bamboo block, washing it twice with ultrapure water until it is neutral, and placing it in a drying oven for constant temperature drying at 50-70°C for 4-8 hours.

9. The antibacterial bamboo material based on L-DOPA and PEI grafted nano-silver coating according to claim 1, characterized in that: Step 1) Cut the bamboo into bamboo blocks with a size of 20×20×6 mm after removing the green bamboo, wash the surface of the bamboo block twice with ultrapure water and anhydrous ethanol respectively to wash away obvious stains on the surface of the bamboo block, then put it into a vacuum drying oven, dry it at 60°C for 72 hours, and then take it out for use. The obtained sample is marked as BT; Step 2) Weigh L-DOPA, pour it into water, add polyethyleneimine (PEI), stir evenly, adjust the solution pH to 8.5 with HCl-Tris buffer solution, and the prepared solution is marked as LD / PEI; Step 3) Add bamboo block BT to the prepared LD / PEI solution, and stir it at a constant temperature in a magnetic stirring oil bath at 60°C for 8 hours. Finally, the stirred bamboo pieces were taken out, washed twice with deionized water, and dried in an oven at 60°C for 6 hours. The obtained samples were marked as BT / LD / PEI respectively. Step 4) AgNO3 was weighed and poured into water. The surface of the beaker was wrapped with tin foil until it was opaque. Then, the samples BT / LD and BT / LD / PEI were respectively placed in a silver nitrate solution, the mouth of the beaker was sealed with tin foil, and the beaker was placed in a magnetic stirring oil bath at 40°C for constant temperature stirring for 6 hours. Finally, the bamboo pieces were taken out, washed twice with ultrapure water until neutral, and dried in a drying oven at 60°C for 6 hours.

10. An antibacterial bamboo material based on L-DOPA and PEI grafted nano-silver coating, characterized in that: The antibacterial bamboo material comprises bamboo material, a polymer film attached to the surface of the bamboo material and nano silver grafted on the surface of the polymer film.